Does neighborhood crime matter? A multi-year survey study on perceptions of race, victimization, and public safety - Cho, Wonhyuk (International journal of law, crime and justice, 2018)
Using multiple large datasets over time from Kansas City, Missouri, hypotheses drawn from theories of racial stereotype amplification, violence desensitization, and dissimilar group threat are tested. The results show that White Americans that live in Black or Hispanic neighborhoods tend to feel less satisfied with public safety, even after controlling for actual crime rates, physical signs of disorder, and a neighborhood's socioeconomic context. However, racial minority residents living in White or minority neighborhoods do not have the same inflated fear. Further, on the issue of race-of-victim effects, the White victimization rate in neighborhoods is found to be negatively associated with public safety perception, whereas the victimization of Blacks has no statistically significant impact. We also found that individuals in Black neighborhood show lower levels of sensitivity to fear of victimization, implying that chronic exposure to neighborhood crime may lead to desensitization.